High aspect ratio electrospun CuO nanofibers as anode material for lithium-ion batteries with superior cycleability - Sahay, Rahul (2013)
A simple and efficient sol–gel/electrospinning technique is employed for the preparation of high aspect ratio CuO nanofibers. Characterizations studies including X-ray diffraction, scanning electron microscopy, High-resolution-transmission electron microscopy are employed to analyze the crystal structure, and morphology of electrospun CuO nanofibers. Electrochemical lithium storage properties are evaluated in half-cell configurations at room temperature between 0.005 and 3 V vs Li. Cyclic voltammetry is used to study the reaction mechanism during charge–discharge process. Electrospun CuO nanofibers delivered stable reversible capacity of 452 mAh g–1 at current density of 100 mA g–1 in half-cell configuration (Li/CuO nanofibers). The cell displayed the very stable cycling behavior up to 100 cycles at current density of 100 mA g–1. Rate capability studies of CuO nanofibers are conducted and presented. Our studies have shown that the enhanced cycleability of CuO electrospun nanofibers are due to the fibrous morphology formed by nanoscopic CuO particles which could not only increase the electrode/electrolyte contact area but also enables the facile partial reduction of Cu2O into metallic particles (Cu0).